BIOTECHNOLOGY FOR INCREASING INULIN CONTENT IN PLANTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Information is provided on plant species containing inulin, their morpho-physiological characteristics, distribution, composition, and plant cultivation technology.